Investigation of Soliton Propagation in Asymmetric metal-dielectric-metal Plasmonics Waveguide - Olyaee, M; Tavakoli, MB; Mokhtari, A (International Journal of Computer Sciences and Engineering, 2025)
In this paper, the propagation of soliton in metal-dielectric-metal (MDM) plasmonics waveguides was investigated for both nonasymmetric and asymmetric structures. Nonasymmetric effects such as Soliton are important for applications such as switching and wavelength conversion. In this paper, it was shown that field enhancement in nonasymmetric MDM waveguides can result in large enhancement of SOLITON magnitude compared to the literature values. Two different structures are considered here as plasmonics waveguide for generation of second harmonic. The first structure is a structure including of a Lithium Niobite as insulator sandwiched between two same metals. Thereafter, two different metals on both sides of the waveguide were used. Besides the structure has grating on both sides for more coupling between photons and plasmons. the wavelength The duration of grating per length unit (number of grooves) will be optimized to reach the highest second harmonic generation. To perform this optimization, the wavelength of operation of λ=458 nm is considered. It was shown that this asymmetric device results in more than two orders of magnitude enhancement in SOLITON compared to a structure with the same metals. It is also shown that the electric field of second harmonic depends on the thickness of crystal (insulator). So, its thickness is optimized to achieve the highest electric field.